ANALISIS MEDIA PEMBELAJARAN IPA MATERI POKOK CIRI-CIRI MAKHLUK HIDUP DI KELAS III MIS PALAMA KOTA BIMA - Putri, Kiki Afriani; Indriani, Irma (JEMARI : Jurnal Edukasi Mahasiswa Sunan Giri, 2023)
This research aims to find out what media is used by an educator in science subjects and specifically focuses on the characteristics of living things. The approach used in this research is qualitative, descriptive in nature, data collection was carried out using interview techniques. The interview technique used was interviewing class III science subject teachers at MIS Palama. The next activity is that the data is processed using data reduction, data display, and drawing conclusions/verification. The research results showed that at MIS Palama there were very minimal school facilities and infrastructure so that teaching and learning activities were not effective and efficient.